The Teaching of Latin and History of Ideas. The Revolution of Port-Royal and its Influence in France and Spain during XVIII Century (Minerva, 2019)
The grammatical and pedagogical Port- Royal method marked the recovery of the former rationalist doctrine (teaching) by Minerva Brocense and her followers Scioppio, Perizonio, and Vossio,as well as the diffusion of the rationalist method from the end of the XVII to the teaching of Latin and Greek languages, apart from the teaching of modern languages. Progressively, the portroyalist method and its later modifications were replacing the preponderant Jesuit grammar teaching, based in a method inspired by the baroque fraught with precepts, rules and exceptions. It's our purpose in this article analyse the contribution of the port-royalist method to the teaching of latin, as well as its subsequent influence on the composition of numerous grammatical treatises that determined the Latin teaching throughout the XVII and partly the XIX.
Keywords: teaching; Latin grammar; Port-Royal; rationalist; Jesuit; baroque; century XVII and XVIII